Wireless physical layer security using channel state information - Tahir, Mohammad; Jarot, Sigit Puspito Wigati; Siddiqi, Muhammad Umar (2010)
In this paper we consider the problem of secure communication between two nodes, over a fading wireless medium, in the presence of a passive eavesdropper. We propose a scheme that provides security based on transforming the basic signal constellation to a higher order signal constellation with the help of conventional encryption method and then using channel knowledge (i.e. amplitude and phase variation), which is location specific, to distort the constellation of encrypted data. This scheme not only makes the estimation of the constellation difficult but also the type of modulation that is used for the adversary. BER (bit error rate) is used as performance metric. We find that the adversary suffers from high BER as compared to its legitimate counterpart.